2016
DOI: 10.1002/jssc.201501159
|View full text |Cite
|
Sign up to set email alerts
|

Efficient strategy for the selective determination of dopamine in human urine by molecularly imprinted solid‐phase extraction

Abstract: An efficient molecularly imprinted solid-phase extraction protocol was developed for the separation of dopamine (DA) from human urine. After successful validation of the analytical method using high-performance liquid chromatography coupled with fluorescence detection, a new strategy for the selective determination of DA in the presence of norepinephrine and epinephrine in human urine was presented. In the proposed protocol, the LODs and quantification for DA were 166 ± 36 and 500 ± 110 nmol/L, respectively, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 35 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…Nevertheless, the best eluent should be characterized by the highest desorption of analyte in the lowest volume of eluent. In our previous studies, we have showed the importance of scrutinous selection of efficient eluent for each individual imprinted sorbent . Here, for that purpose, 0.08 aq.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the best eluent should be characterized by the highest desorption of analyte in the lowest volume of eluent. In our previous studies, we have showed the importance of scrutinous selection of efficient eluent for each individual imprinted sorbent . Here, for that purpose, 0.08 aq.…”
Section: Resultsmentioning
confidence: 99%
“…As a new separation technique, molecular imprinting can make the active components of natural products highly concentrated with few impurities and effectively improve the purity of products. Molecularly imprinted polymers (MIPs) have shown the important applications for the purification and preconcentration of biomolecules from complex human fluids such as urine or postmortem blood (Lulinski et al, 2015(Lulinski et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the authors of some excellent review papers discussed different formats of MIPs . Also, numerous papers revealed the application of MIPs for the determination of bioanalytes such as bioamines . The MIPs were also successfully applied in fabrication of sensors and drug delivery devices .…”
Section: Introductionmentioning
confidence: 99%